2018
DOI: 10.1159/000489277
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Uptake of Ara h 3 from Raw and Roasted Peanut by Monocyte-Derived Dendritic Cells

Abstract: Roasting has been implicated in the increase of peanut allergenicity due to the chemical reactions that occur during the process. However, this increase is not fully understood, and little information is available regarding the role of roasted peanut allergens in the initial phase of allergy, where dendritic cells (DCs) play a key role. We sought to analyze differences in the internalization of Ara h 3 from raw and roasted peanut by immature monocyte-derived DCs (MDDCs) and the implication of the mannose recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…[ 67 ]) was shown [ 68 ]. Binding of roasted Ara h 1 was shown to occur to scavenger receptor CD36 and receptor for advanced glycated end products RAGE [ 69 , 70 ], and for roasted Ara h 3 to mannose receptor [ 71 ]. Most importantly, this engagement leads to cellular signaling resulting in pro-inflammatory responses and enhanced allergic sensitization, as was shown in a mouse model comparing raw vs. roasted peanut [ 69 ].…”
Section: Digestion and Digestibility Of Proteins Associated With Lmentioning
confidence: 99%
“…[ 67 ]) was shown [ 68 ]. Binding of roasted Ara h 1 was shown to occur to scavenger receptor CD36 and receptor for advanced glycated end products RAGE [ 69 , 70 ], and for roasted Ara h 3 to mannose receptor [ 71 ]. Most importantly, this engagement leads to cellular signaling resulting in pro-inflammatory responses and enhanced allergic sensitization, as was shown in a mouse model comparing raw vs. roasted peanut [ 69 ].…”
Section: Digestion and Digestibility Of Proteins Associated With Lmentioning
confidence: 99%
“…This could be due to the number of samples used, and a more thorough analysis will be necessary in the future. In our previous study with Ara h 3, we found a statistically significant increase in the internalization of purified Ara h 3 from roasted peanuts compared to Ara h 3 purified from raw peanuts [21]. These apparent differences between Ara h 2 and Ara h 3 might be explained by the different effects that the roasting process has on both allergens.…”
Section: Discussionmentioning
confidence: 77%
“…After these analyses, the purities of Ara h 2 from raw and roasted peanuts were found to be greater than 95%. Ara h 2 purified from raw and roasted peanuts, raw-Ara h 2, and roast-Ara h 2, respectively, were labeled with the fluorescent dye DyLight amine-reactive dye 488 NHS (Thermo Fisher Scientific, Bremen, Germany) as previously described [21]. The raw-Ara h 2 and roast-Ara h 2 labeled with the fluorescent dye were stored protected from light at −20 • C until use.…”
Section: Ara H 2 Purification From Raw and Roasted Peanuts And Labelimentioning
confidence: 99%
See 1 more Smart Citation
“…From the linear sequence of Ara h 3, 3D models have been developed [ 28 ] and the crystal structure has been solved [ 29 ]. It is important to note that it has been shown that monocyte-derived dendritic cells, which are antigen presenting cells, display differential uptake of Ara h 3 purified from raw (R), light roast (LR) and dark roast (DR) peanuts [ 30 ]. In this study, we investigated differently processed Ara h 3 at the molecular level.…”
Section: Introductionmentioning
confidence: 99%